2019
DOI: 10.1016/j.pnpbp.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of psychopathological dimensions shared between schizophrenia and bipolar disorder

Abstract: Shared genetic vulnerability between schizophrenia (SCZ) and bipolar disorder (BP) was demonstrated, but the genetic underpinnings of specific symptom domains are unclear. This study investigated which genes and gene sets may modulate specific psychopathological domains and if genome-wide significant loci previously associated with SCZ or BP may play a role. Genome-wide data were available in patients with SCZ (n = 226) or BP (n = 228). Phenotypes under investigation were depressive and positive symptoms sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
(91 reference statements)
2
6
0
Order By: Relevance
“…Endophilin A1 is a member of the endophilin A protein family characterized by an amino-terminal N-BIN/amphiphysin/Rvs (BAR) domain and a carboxyl-terminal Src homology 3 (SH3) domain. The gene encoding endophilin A1 ( EEN1 , gene name sh3gl2 ) is almost exclusively expressed in brain ( Ringstad et al, 1997 ) and has been implicated in epilepsy, schizophrenia, and Alzheimer’s disease ( Corponi et al, 2019 ; Ren et al, 2008 ; Yu et al, 2018a ; Yu et al, 2018b ). Originally identified as a component of the endocytic machinery, endophilin As function in synaptic vesicle recycling ( Milosevic et al, 2011 ; Ringstad et al, 1997 ; Schuske et al, 2003 ; Verstreken et al, 2003 ; Watanabe et al, 2018 ), autophagosome formation, and protein homeostasis at presynaptic terminals ( Murdoch et al, 2016 ; Soukup et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endophilin A1 is a member of the endophilin A protein family characterized by an amino-terminal N-BIN/amphiphysin/Rvs (BAR) domain and a carboxyl-terminal Src homology 3 (SH3) domain. The gene encoding endophilin A1 ( EEN1 , gene name sh3gl2 ) is almost exclusively expressed in brain ( Ringstad et al, 1997 ) and has been implicated in epilepsy, schizophrenia, and Alzheimer’s disease ( Corponi et al, 2019 ; Ren et al, 2008 ; Yu et al, 2018a ; Yu et al, 2018b ). Originally identified as a component of the endocytic machinery, endophilin As function in synaptic vesicle recycling ( Milosevic et al, 2011 ; Ringstad et al, 1997 ; Schuske et al, 2003 ; Verstreken et al, 2003 ; Watanabe et al, 2018 ), autophagosome formation, and protein homeostasis at presynaptic terminals ( Murdoch et al, 2016 ; Soukup et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CLDN7 was found upregulated in mouse pancreas exposed to caerylein for 12 h and its function concerned tight junction formation, while destruction of tight might be closely related with autophagy’s detrimental effects ( Nakada et al, 2010 ; Wang S. et al, 2020 ). So far CLVS1 wasn’t found significant in tumorigenesis and progression, but research found it is involved in lysosome maturation and associated with psychiatric and steroid-sensitive nephrotic syndrome ( Corponi et al, 2019 ; Lane et al, 2021 ). GMIP is a protein coding gene that encodes ARHGAP family of Rho/Rac/Cdc42-like GTPase activating proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Endophilin A1 (EPA1) plays a crucial role in the regulation of nervous system diseases and tumor diseases [2,3]. Its structure includes an aminoterminal N-BIN/amphiphysin/Rvs (BAR) domain and a carboxy-terminal Src homology region 3 (SH3) domain, encoded by the SH3GL2 gene and expressed almost exclusively in the brain, and is associated with epilepsy and schizophrenia [4,5]. In addition to being associated with Alzheimer's disease (AD) [6,7], SH3GL2 was designated as a risk locus for PD by genome-wide association analysis [8].…”
Section: Introductionmentioning
confidence: 99%